The long-term impact of adverse caregiving environments on epigenetic modifications and telomeres - Blaze, Jennifer; Asok, Arun; Roth, Tania L. (Frontiers in Behavioral Neuroscience, 2015)
Early childhood is a sensitive period in which infant-caregiver experiences have profound effects on brain development and behavior. Clinical studies have demonstrated that infants who experience stress and adversity in the context of caregiving are at an increased risk for the development of psychiatric disorders. Animal models have helped to elucidate some molecular substrates of these risk factors, but a complete picture of the biological basis remains unknown. Studies continue to indicate that environmentally-driven epigenetic modifications may be an important mediator between adverse caregiving environments and psychopathology. Epigenetic modifications such as DNA methylation, which normally represses gene transcription, and microRNA processing, which interferes with both transcription and translation, show long-term changes throughout the brain and body following adverse caregiving. Recent evidence has also shown that telomeres (TTAGGG nucleotide repeats that cap the ends of DNA) exhibit long-term changes in the brain and in the periphery following exposure to adverse caregiving environments. Interestingly, telomeric enzymes and subtelomeric regions are subject to epigenetic modifications – a factor which may play an important role in regulating telomere length and contribute to future mental health. This review will focus on clinical and animal studies that highlight the long-term epigenetic and telomeric changes produced by adverse caregiving in early-life.